Investigação epistemológica sobre as dualidades conceptuais normal/patológico e saúde/doença em Freud: uma perspectiva lewiniana - Albuquerque, Kelly Moreira de (2012)
We search here about two kinds of conceptual dualities in Freud: health/disease and normality/pathology. By means of Kurt Lewin’s epistemological perspective, we seek to know how these dualities could correspond to Galilean and Aristotelian ways of scientific thought. Having evidenced that Freud had shown an oscillation between the modes of scientific thought, we have sought, through Freud’s own works, some indication which would help as a supplementary Galilean reference. We considerate, then, that Freud’s view on plasticity and adhesiveness of libido present the idea of a continuum between the two phenomena. That is, instead of opposing them in the way of the Aristotelian dichotomies, Freud has dialectically connected them as dualities and series of phenomena which show internal and continuous variation among themselves. This testifies the existence of some phases of transition between normality and pathology and health and disease. Once Freud had only conceived but never formalized his idea in epistemological terms, we have tried to do this. By means of Canguilhem theory life normativity and the differences between normality and health as well as abnormality and pathology, we have found out that: (1) the above mentioned dualities correspond to the Galilean way of thought; this occurs mainly when Freud refers to neurosis; Freud conceived them as a series of phenomena that show internal and continued interconnection. (2) Despite the difference between their fields of reference, the logic found in Freud is somewhat comparable to what Canguilhem attributed to life normativity.